Analisis Pengendalian Persediaan Obat Antibiotik Menggunakan Metode EOQ pada Instalasi Farmasi RS Hikmah Makassar Kota - Radysa Puteri Maharani; Nur Afiah; Samsinar Samsinar (AKUNTANSI 45, 2026)
This study aims to analyze the application of the Economic Order Quantity (EOQ) method in controlling antibiotic drug inventory at the Pharmacy Installation of Hikmah Hospital, Makassar City. The research employs a descriptive quantitative approach, with data collected through inventory documentation and interviews with pharmacy staff. The analysis was conducted by identifying inventory requirements and costs, calculating EOQ variables, and comparing the results with the conventional inventory control system implemented by the hospital. The findings indicate that the EOQ method is more optimal than the conventional method, as it significantly reduces total inventory costs. The EOQ calculation resulted in an optimal order quantity ranging from 16 to 160 units per antibiotic item, with the ordering frequency decreasing from 36 times to 20 times. The safety stock calculation, based on a 98% service level and a two-day lead time, produced a safety stock of 1–130 units and a reorder point of 2–193 units. The total inventory cost using the EOQ method amounted to Rp 478,725, which is lower than the conventional method at Rp 554,437, resulting in cost savings of Rp 75,712 or 13.7%. These findings demonstrate that the integrated implementation of the EOQ method enhances inventory control efficiency and ensures the availability of antibiotic drugs.